Bone fragility and sarcoidosis: An underestimated relationship - Caffarelli, Carla; Cameli, Paolo; Al Refaie, Antonella; Giglio, Elisa; Manzana, Giulio; Mondillo, Caterina; Noacco, Yari; Olivieri, Carmela; Bargagli, Elena; Gonnelli, Stefano (Frontiers in Medicine, 2022)
Introduction Sarcoidosis is a chronic multisystem inflammatory disease which may affect any organ. Also bone can be involved both directly and indirectly. Data on BMD values and fragility fractures in sarcoidosis patients are few and heterogeneous. This study aimed to characterized the presence of fracture and the relative risk factors in patients with sarcoidosis. Materials and methods In this single center cross-sectional study we evaluated 252 sarcoidosis patients (54.7 ± 12.1 years) compared to sex-and age matched healthy controls. We measured BMD at lumbar spine, at femoral neck and at total hip. Moreover, the presence of fragility fractures was collected during osteoporosis visit and all radiological images were examined for the presence of any vertebral fracture according to Genant’s method’s. Lung function measurements, including forced expiratory volume in one second (FEV1), forced vital capacity (FVC), FEV1/FVC, and diffusion capacity for carbon monoxide (DLCO) were assessed. Results Bone Mineral Density T-scores were lower in patients affected by sarcoidosis with respect to those obtained in healthy controls, but the difference was statistically significant only for BMD-LS (p < 0.01) and BMD-TH (p < 0.05). Moreover, BMD values at all skeletal sites were significantly associated with DLCO (%) (p < 0.05). The prevalence of fragility fracture was higher in patients with sarcoidosis than in healthy controls (30.6 vs. 12.3%). The patients with ≥3 vertebral fracture had lower values of FVC (%), FEV1 (%), and DLCO (%). Multiple regression analyses showed that BMI was positively associated with fragility fracture, while BMD-TH, DLCO(%) and therapy use was negatively associated. Conclusions Vertebral fractures represent a frequent complication in patients with sarcoidosis. Furthermore, the number of vertebral fractures was linked with a worsening in pulmonary functional tests. Therefore, the degree of severity of the sarcoidosis disease appears to be the main determinant of bone fragility.